Liquid crystal optical fiber sensor based on misaligned core configuration for temperature and mixed volatile organic compound detection. (December 2022) - Zhou, Dong; Lan, Zeqing; Cao, Wenzhu; Chen, Yuzhou; Zhang, Shushen; Hu, Jianyang; Shang, Jianyu; Peng, Zenghui; Liu, Yongjun
Abstract: In this paper, an optical fiber sensor based on cholesteric liquid crystal (CLC) is used for real-time monitoring of temperature and volatile organic compound (VOC) gas concentration. The sensor works based on a 2 × 2 multimode fiber coupler whose two output ports can respectively function as gas and temperature sensor probes. The former was realized by dislocation fusion of two multimode fibers (MMFs) coated with two CLCs, and the CLC reflection peak has a red shift with the increasing concentrations of acetone and tetrahydrofuran (THF) gas. The other MMF port has been fused with hollow capillary fibers (HCF). To eliminate the adverse effects of external temperature fluctuations, the enclosed CLC in the HCF will realize real-time temperature monitoring and temperature compensation. In addition, the sensor can also measure the dependence of the wavelength on the total gas concentration of different mixing ratios of acetone and THF, and distinguish the concentration of acetone and THF in the mixed gas.